The Effect of Biotechnology Learning using Pulau Tunda’s Local Potential on Students’ Creative Thinking Skills - Iis Rusmiyati; Siti Gia Syauqiah Fitri; Indah Juwita Sari (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
This study aimed to determine the effect of learning using local potential of Pulau Tunda on the creative thinking skills of class XII students on biotechnology concept. The method used is quasi-experimental and research design used in this study is a posttest-only control design. The independent variable in this study is Biotechnology learning using local potential of Pulau Tunda while the dependent variable is the creative thinking skills. The subject in this study were students at one high school in Indonesia consists of two classes, namely class XII IPA 2 as an experimental class and XII IPA 3 as a control class. The sampling technique is done simply random sampling. Data were collected through posttest to measure students' creative thinking skills and student response questionnaires Ability results creative thinking was analyzed using the t-test. Based on those results that there is an influence of learning with the utilization of the local potential of the Pulau Tunda on students' creative thinking skills on biotechnology concept.